A health economic evaluation of needle-based confocal laser endomicroscopy for the diagnosis of pancreatic cysts - Claude Le Pen; Laurent Palazzo; Bertrand Napoléon (Endoscopy International Open, 2017)
Background and study aims The low sensitivity of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA), especially for the diagnosis of serous cystadenomas (SCAs), can be associated with diagnostic uncertainty that can regularly lead to unnecessary surgical procedures. Needle-based confocal laser endomicroscopy (nCLE) used with EUS-FNA improves diagnostic accuracy, helping to reduce unnecessary surgery and patient follow-up. This study was conducted to evaluate the economic benefit of EUS-FNA + nCLE. Patients and methods Probabilities used were derived from two studies representative of the two diagnostic strategies: a retrospective analysis of patients diagnosed by EUS-FNA alone and a prospective study of patients diagnosed by EUS-FNA + nCLE. Costs were based on French healthcare system rates; both private and public sector rates were included. A decision tree structure model used these probabilities and costs for two hypothetical cohorts of 1000 patients. Results EUS-FNA + nCLE resulted in a reduction of 23 % in the total rate of surgical intervention, which translated to a reduction in clinical costs of 13 % (public sector) and 14 % (private sector). Additionally, the reduced rate of surgery would save the lives of 4 in 1000 patients. A stochastic sensitivity analysis using 100 simulations showed that in all cases the number of interventions was less for EUS-FNA + nCLE than for EUS-FNA. There was also a reduction in the incidence of false negatives using EUS-FNA + nCLE. Conclusions EUS-FNA + nCLE results in significant economic benefits by reducing the incidence of misdiagnosis through improved diagnostic accuracy.